Unit operations of chemical engineering - McCabe, Warren Lee, 1899-1982; Harriott, Peter, 1927-; Smith, Julian Cleveland, Jr., 1919-2015 (Boston : McGraw-Hill, 2001)
The book is written in a practical manner for the education of B.S. level chemical engineers. It introduces students to common equipment and gives them the basic concepts of operation both qualitatively and quantitatively. A solid theoretical foundation enables students to understand basic phenomena underlying the unit operations but real-world applications are also sufficiently covered.